2001
DOI: 10.1001/archotol.127.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Management of Orbital Subperiosteal Abscess in Children

Abstract: Bilateral pansinusitis was the most common cause. All patients received an initial trial of intravenous antibiotics. Based on the Fisher exact test, no statistically significant differences were detected for age, sex, presence of gaze restriction, and radiographic findings. Based on multiple logistic regression, degree of proptosis was the only significant multivariate predictor of surgery (P =.003). The estimated probability of surgery was 6% when there was no proptosis, and 92% for 2 mm of proptosis. The loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
113
2
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 19 publications
5
113
2
10
Order By: Relevance
“…[2][3][4] In the past decade, endonasal techniques replaced the traditional external surgical approaches to manage the majority of these complications. 5,6 Indeed, endoscopic sinus surgery (ESS) has provided effective and safe options for managing sinogenic complications of the orbit, frontal sinus, and anterior skull base that would previously have necessitated extensive open approaches. [7][8][9][10][11] However, certain regions involved in pathology of the sinuses either cannot be accessed in this fashion or they endanger critical neurovascular structures when transnasal pathways are employed.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In the past decade, endonasal techniques replaced the traditional external surgical approaches to manage the majority of these complications. 5,6 Indeed, endoscopic sinus surgery (ESS) has provided effective and safe options for managing sinogenic complications of the orbit, frontal sinus, and anterior skull base that would previously have necessitated extensive open approaches. [7][8][9][10][11] However, certain regions involved in pathology of the sinuses either cannot be accessed in this fashion or they endanger critical neurovascular structures when transnasal pathways are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, despite antimicrobial and surgical management, 15% to 30% of patients with an SPA develop various visual sequelae. [3] Overtime, the number of orbital complications has reduced, however, the orbital complications of acute rhinosinusitis are still dreaded.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that there is no significant difference in the failure rates of transnasal endoscopic, external or combined approaches. 5,14 In our clinic, we applied medical treatment with a combination of ampicillin and beta lactamase inhibitors with metronidazole, and performed surgical intervention when a subperiosteal developed and was resistant to medical treatment. 15,16 We performed functional sinus surgery combined with external orbitotomy in two cases of whom the CT scans showed ethmoiditis whereas in one case, external orbitotomy was performed alone as it was superiorly located and endoscopically unapproachable.…”
Section: Discussionmentioning
confidence: 99%